A Analysis of Mathematics Teacher Difficulties in Implementing 2013 Curriculum Online: Analysis of Mathematics - Halomoan, Jitu; Male, Hendrikus (International Journal of Business, Law, and Education, 2022)
ABSTRACT Research to see the difficulties of online learning. Survey of the Indonesian Ministry of Education 2020, 58% ineffective learning process, 38% lack of guidance, 35% poor communication, 62% need internet access, 59.5% object to school assignments. Research aims; 1) knowing the online learning process, 2) knowing the assessment method, 3) knowing how difficult it is for the teacher to prepare the material. Descriptive qualitative method by collecting data from observations and interviews, analysis techniques by presenting data, reduction and conclusions. The results of observational analysis and interview results 95% of the learning process still adopts curriculum 13. Students think that the teacher does not have a module as a tool for the learning process, the teacher's difficulty lies in writing integral symbols, logarithms, matrices and mathematical induction on google meet. The teacher prepares the RPP, however, the RPP given does not represent the textbook. The book given the concept is too difficult, the impact is that students only hear and receive answers from the teacher without any active interaction. 3) 60% of students disagree with the assessment method, the material being tested is more difficult than what is taught, as a result, learning outcomes are not as expected. The teacher has difficulty operating the google meet media, the teacher does not master how to write symbols, the difficulty of proving formulas, the difficulty of providing concepts, the difficulty of the internet network, the difficulty of correcting assignments, the difficulty of applying the Student center learning method, as a result the RPP designed is not in accordance with the implementation. Assessment, 45% of students do not agree with the pedagogy. Conclusion